The PTEN/PI3K/AKT Pathway in vivo, Cancer Mouse Models - Carnero, Amancio; Paramio, Jesus M. (Frontiers in Oncology, 2014)
PTEN negatively regulates PI3K signalling by dephosphorylating PIP3 to PIP2. AKT is activated downstream of PIP3 to mediate physiologic processes. Furthermore, substantial crosstalk exists with other signalling networks at all levels of the PI3K pathway. As a consequence of diverse gene mutations and amplifications, and also due to its central role in several signal transduction pathways, the PI3K-dependent axis is frequently overactivated in a huge variety of human tumors, thus becoming an attractive therapeutic target. The preclinical testing of such therapies requires adequate and well tailored systems for their analysis. Mouse models with genetic modifications in the pathway have been essential to identify the role of this pathway in the tumorigenesis process. Here we review genetically modified models of cancer by modifying the PI3K/AKT pathway.